The everything guide to spices for health : a complete guide to the natural health-boosting benefits of everyday spices - Robson-Garth, Michelle, (Everything, 2016)
"Discover the amazing powers of spices and herbs!Spices have long been celebrated for their antioxidant, anti-inflammatory, and curative properties. From increasing energy to boosting metabolism and relieving joint aches, spices can help you improve your body, mind, and spirit. In The Everything Guide to Spices for Health, you'll learn how to tap into these benefits and promote overall wellness with uses for dozens of popular herbs and spices, including oregano, sage, chili pepper, and saffron.Inside, you'll find more than 50 wholesome, health-boosting recipes, such as: Turmeric, Apple, and Carrot Juice Szechuan Pepper Chicken and Noodle Soup Basic Indian-Style Curry with Lamb Spiced Coconut and Date "Bliss" Balls Rose, Elder Flower, and Hawthorn Tea Sumac and Walnut Salad So get ready to spruce up the spice rack and start reaping the incredible benefits of these kitchen staples. With this book, you'll find it easier than ever to incorporate delicious, health-boosting herbs and spices into your diet!"--